2020
DOI: 10.1186/s12889-020-08965-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an mHealth voice message service (mMitra) on maternal health knowledge and practices of low-income women in India: findings from a pseudo-randomized controlled trial

Abstract: Background: Mobile Health (mHealth) is becoming an important tool to improve health outcomes in maternal, newborn and child health (MNCH). Studies of mHealth interventions, have demonstrated their effectiveness in improving uptake of recommended maternal services such as antenatal visits. However, evidence of impact on maternal health outcomes is still limited. Methods: A pseudo-randomized controlled trial (single blind) was conducted to assess the impact of a voicemessage based maternal intervention on matern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 14 publications
(18 reference statements)
1
47
0
Order By: Relevance
“…In the Wired Mothers study, the intervention group receiving SMS reminders had a significantly higher percentage of women delivering with skilled birth personnel (60%) compared to the control group (47%) ( 48 ). The use of apps in combination with SMS or voice reminders has also been proven to significantly increase supervised institutional deliveries in three studies ( 45 , 53 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Wired Mothers study, the intervention group receiving SMS reminders had a significantly higher percentage of women delivering with skilled birth personnel (60%) compared to the control group (47%) ( 48 ). The use of apps in combination with SMS or voice reminders has also been proven to significantly increase supervised institutional deliveries in three studies ( 45 , 53 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…The RCT presented here is part of a large mixed methods evaluation of Kilkari 17. Findings add to the limited evidence available on the effectiveness of large-scale health information messaging programmes4 7 12 and smaller scale initiatives in Malawi8 and Zanzibar 9–11. However, comparisons with other programmes are challenging given the fundamental differences in programme components, implementation partners, study contexts, scale of implementation and evaluation design.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence linking scaled mHealth messaging programmes to changes in health outcomes is limited [7][8][9][10][11][12] ; a factor which may impede sustainability and further expansion. 13 The…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 There have been a few systematic reviews evaluating the role mHealth plays in improving the health care system especially in developing countries. Murthi et al 11 concluded that mobile voice messages provided suitable and appropriate information throughout pregnancy and helped improve uptake of maternal services geared towards improving maternal health outcomes. Free et al7 too found advantages related with mHealth interventions as it concerns utilization of health services especially in the area of appointment reminders and provision of related clinical support.…”
Section: Introductionmentioning
confidence: 99%